Studies of Sr2+ ion substitution on ferroelectric and piezoelectric properties of PZT nanocrystalline - Kour,P. (2013)
Strontium substituted lead zirconate titanate nanocrystalline material with chemical formula Pb0.95Sr0.05 (Zr0.52Ti0.48) O3 have been synthesized by alkoxide based sol gel method. The product was characterized by differential thermal analysis, thermogravimetric analysis, powder X-ray diffraction and scanning electron microscopy. The ferroelectric hysteresis loop measurement was carried out at room temperature using ferroelectric loop tracer over a field range of 20 kV/cm. The remanent polarization Pr, saturation polarization Pmax and coercive field Ec were 12.97 µC/cm², 30.52 µC/cm² and 6.5 kV/cm respectively. The piezoelectric coefficient d33 was measured with the variation of polling field.